2018
DOI: 10.3329/bjz.v46i2.39047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ectoparasites in cattle (Bos indicus) of Jessore, Bangladesh

Abstract: A study was carried out on 60 cattle and 34 (56.66%) were found infested with ticks and lice. Mean parasitic burden was 2.26  0.37 per square inches in cattle. Two species of arachnids, Haemaphysalis bispinosa (31.66%) andRhipicephalus sanguineus (28.33%) lice, Linognathus vituli (23.33%) were identified. Mean parasitic burden was high in case of R. sanguineus (4.33  0.48) followed by H. bispinosa (2.89 ± 0.62) and least in L. vituli (1.28 ± 0.16). Prevalence of ectoparasites were relatively higher in young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 5 publications
3
6
0
Order By: Relevance
“…The study in Dhaka Metropolitan area revealed a considerable prevalence of ectoparasites among companion animals, with rates of 59.57% in dogs and 61.25% in cats, reflecting a substantial burden on urban pets. These rates align with global concerns, mirroring high infestation rates reported in similar studies, such as Alho et al (2018) in Qatar and Sharmin et al (2018) in Bangladeshi cattle. Cats showed higher vulnerability than dogs, consistent with findings from other studies, including Sharmin et al (2018), highlighting the broader issue of ectoparasite prevalence within the country.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The study in Dhaka Metropolitan area revealed a considerable prevalence of ectoparasites among companion animals, with rates of 59.57% in dogs and 61.25% in cats, reflecting a substantial burden on urban pets. These rates align with global concerns, mirroring high infestation rates reported in similar studies, such as Alho et al (2018) in Qatar and Sharmin et al (2018) in Bangladeshi cattle. Cats showed higher vulnerability than dogs, consistent with findings from other studies, including Sharmin et al (2018), highlighting the broader issue of ectoparasite prevalence within the country.…”
Section: Discussionsupporting
confidence: 83%
“…These rates align with global concerns, mirroring high infestation rates reported in similar studies, such as Alho et al (2018) in Qatar and Sharmin et al (2018) in Bangladeshi cattle. Cats showed higher vulnerability than dogs, consistent with findings from other studies, including Sharmin et al (2018), highlighting the broader issue of ectoparasite prevalence within the country.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These months are considerably cooler than the other months of the year in the Philippines. In warmer months, higher tick prevalence rates are usually reported in other countries [27,28]. The lack of tick vector in this study could have lowered the chances of the goats to acquire the pathogens.…”
Section: Resultsmentioning
confidence: 61%
“…Even with basic veterinary measures, permanent ectoparasites can infect livestock, as animals experience more intense hair growth during the winter stall period. In the absence of sufficient insolation, even this physiological feature of the body contributes to outbreaks of diseases caused by permanent ectoparasites [11,12]. During the stall period, significant damage to livestock is caused by permanent parasites -lice and hair follicles, which cause sifunculatosis and bovicolosis disease [13,14].…”
Section: Introductionmentioning
confidence: 99%